Changes of Haccp systemin a dairy farm due to the installment of automatic milking system - Lencsés, Enikő; Kovács, Attila; Dunay, Anna; Mészáros, Kornélia (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The main aim of this study is to summarize the steps of work of automatic milking system. The milking system is used in Experimental and Demonstration Farm of Józsefmajor of the Szent István University of Gödöllő. This diary farm produces fresh milk. The automatic milking robot is unique in Hungary. The HACCP System was installed more than ten years ago to improve the quality of the produced milk and to meet the EU requirements. The installation of milking robot has changed the steps of the HACCP System and has made the milking process more simple and safety. On the other hand, due to the fully automatic milking process there are less physical and biological critical points. In summary, automatic milking system helps to harmonize the milking, feeding and relaxing period of the herd, and also makes the compliance with food safety regulations easier. The second aim of the paper is to define the possible cost-benefit changes due to the automatic milking system on the dairy farm.
Keywords: cost-benefit analysis; milk production; VMS; food safety